Laying the Foundation for Early Childhood Education in Sri Lanka : Investing Early, Investing Smartly, and Investing for All - World Bank Group (World Bank, Washington, DC, 2015)
The objective of this report is to analyze the state of early childhood education (ECE1) provision and the policy framework for delivering ECE in Sri Lanka, and suggest policy options for the future. The report is intended to serve several purposes. First, drawing upon the international literature in the field of early childhood development, it provides the rationale for investing in early childhood education in Sri Lanka. Second, it provides an understanding of the current policy framework and delivery system for ECE in the country. This policy analysis specifically looks at the extent to which there is an enabling environment for ECE, what provisions exist for monitoring and quality assurance, and how widely the policy is being implemented. Third, it presents a situation analysis of ECE provision in Sri Lanka, discussing the issues of access, equity, and quality in the delivery of ECE services. The discussion on equity focuses mainly on understanding disparities in access, and the analysis of quality looks at the quality of inputs, processes and outcomes, including cognitive and non-cognitive outcomes. And fourth, the report presents policy and program options based on the findings of the above analyses.